The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1981
DOI: 10.1111/j.1600-0765.1981.tb01001.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of subclinical ascorbate deficiency on periodontal health in nonhuman primates

Abstract: The aim of this study was to evaluate the effects of chronic subclinical ascorbic acid deficiency on periodontal health in a nonhuman primate model. Young adult Macaca fascicularis monkeys were fed an ascorbic acid free diet for nine weeks followed by a diet with a suboptimal level of ascorbic acid for an additional sixteen weeks. During the 25‐week period, a pair fed control group was fed a nutritionally adequate diet in amounts equivalent to that consumed by the experimental group. From the second week onwar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
3

Year Published

1984
1984
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 21 publications
0
15
0
3
Order By: Relevance
“…PMN chemotaxis in monkeys was not monitored and whether defective PMN chemotaxis could influence the onset of disease in these animals is unknown at the present time. Periodontal destruction in scorbutic monkeys may, at least in part, be due to this complication (Alvares et al, 1981). The third possible explanation is that A. actinomycetemcomitans can initiate periodontal problems, but tissue destruction is minimized because monkeys develop an effective antibody response to such challenge and thereby limit the chance of developing clinically-significant lesions.…”
Section: Discussionmentioning
confidence: 99%
“…PMN chemotaxis in monkeys was not monitored and whether defective PMN chemotaxis could influence the onset of disease in these animals is unknown at the present time. Periodontal destruction in scorbutic monkeys may, at least in part, be due to this complication (Alvares et al, 1981). The third possible explanation is that A. actinomycetemcomitans can initiate periodontal problems, but tissue destruction is minimized because monkeys develop an effective antibody response to such challenge and thereby limit the chance of developing clinically-significant lesions.…”
Section: Discussionmentioning
confidence: 99%
“…However, contemporary studies suggest that the various forms of gingivitis and periodontitis result mainly from the activities of certain oral micro-organisms that colonize the teeth and adjacent periodontal tissues (Socransky, 1977;Page and Schroeder, 1982;Williams, 1990). A secondary role in the infectious process has been postulated for ascorbic acid deficiency (Dreizenet al, 1969;Alvares et al, 1981), but most of the epidemiological and experimental evidence accumulated in the last several decades has failed to demonstrate any significant etiological relationship between ascorbic acid deficiency and the periodontal diseases (Russell, 1963;Enwonwu and Edozien, 1970;Robinson, 1977;Woolfe et al, 1980;Ismail et al, 1983;Vogel et al, 1986).…”
Section: Introductionmentioning
confidence: 97%
“…Alvares et al [ 5 ] evaluated the effects of chronic subclinical ascorbic acid defi ciency on periodontal health in a monkey model and found that gingival index (GI) [ 46 ] score and PPD were signifi cantly greater in the ascorbate defi cient animals than in the controls. Recent animal studies indicated the effi cacy of vitamin C in improving periodontal disease.…”
Section: Animal Studies On the Effects Of Vitamin C On Periodontal Dimentioning
confidence: 98%